Factores Pedagógicos - Psicosociales Y Su Incidencia En El Rendimiento Académico De Los Educandos De La Unidad Educativa “Seis De Octubre” De La Ciudad De Ventanas, Provincia De Los Ríos - Paredes Borja, Emma E. (2015)
This research is a didactic-pedagogical compendium prepared to implement in the learning process of students SCHOOL DR. OSWALDO HURTADO LARREA CANTON MIRACLE, confident that the implementation of these strategies will develop significant learning basic skills specified in the Upgrading and Strengthening Curriculum of General Basic Education, and thinking that it is inscribed within the broader criterion of recreational endeavor Good Live. The methodological strategies are teaching guidelines that every teacher should be applied in the teaching-learning process built for themselves what makes that students relate and grow, its context, and put very high values, both moral, ethical and spiritual society, it is our obligation and need to develop an active education in the classroom. Teaching is a skill that we have professional teachers of basic education related to communication, are different each requires a differentiated treatment as psycho communicative act requires different rules in each of the extracts of language combination. It is important to remember that the methodological strategies help students develop logical, critical and creative thinking, this helps to create a better future society with elements that will contribute to the socioeconomic development of the country, with ethical and moral values, and of critical thinking and not rote.